Useful Irregularity Indices in QSPR Study for Bismuth Tri-Iodide - Abaid ur Rehman Virk; M. A. Rehman; Ce Shi; Waqas Nazeer (Journal of Chemistry)
Topological indices give us a mathematical language to study molecular structures. They convert a chemical compound into a single number which foresees properties, for example, boiling points, viscosity, and the radius of gyrations. Drugs and other chemical compounds are often modeled as various polygonal shapes, trees, and graphs. In this paper, we will compute some irregularity indices for bismuth tri-iodide chain and sheet that are useful in the quantitative structure-activity relationship.